Protocol to assess performance of crisis standards of care guidelines for clinical triage - Louis T. Merriam (Elsevier, 2021)
Summary: During the COVID-19 pandemic, US states developed Crisis Standards of Care (CSC) algorithms to triage allocation of scarce resources to maximize population-wide benefit. While CSC algorithms were developed by ethical debate, this protocol guides their quantitative assessment. For CSC algorithms, this protocol addresses (1) adapting algorithms for empirical study, (2) quantifying predictive accuracy, and (3) simulating clinical decision-making. This protocol provides a framework for healthcare systems and governments to test the performance of CSC algorithms to ensure they meet their stated ethical goals.For complete details on the use and execution of this protocol, please refer to Jezmir et al. (2021).